Dietary Agonists of TRPV1 Inhibit Gastric Acid Secretion in Mice - Okumi, Hirokuni; Tashima, Kimihito; Matsumoto, Kenjiro; Namiki, Takao; Terasawa, Katsutoshi; Horie, Syunji (Planta Medica, 2012)
Capsaicin and 6-gingerol, pungent components of chilli pepper and ginger, are known as dietary agonists of transient receptor potential vanilloid-1. Transient receptor potential vanilloid-1 nerve fibers are recognized to play a role in gastric mucosal integrity in rats. In the present studies, we examined the acute effects of peroral administration of capsaicin and 6-gingerol on gastric acid secretion in conscious mice. These agents were given p. o. 30 min before the pylorus was ligated. Oral administration of capsaicin (1.0–100 mg/kg) or 6-gingerol (1.5–50 mg/kg) significantly and dose-dependently inhibited basal acid secretion. Pretreatment with BCTC, a transient receptor potential vanilloid-1 antagonist, significantly reversed the reduced basal acid secretion by capsaicin or 6-gingerol. The combination of the lowest doses of capsaicin and 6-gingerol markedly inhibited basal acid secretion in conscious mice and this was also significantly reversed by BCTC. Moreover, the combination of the maximal dose of capsaicin and 6-gingerol inhibited basal acid secretion only to the level of a single administration of the maximal dose of capsaicin. These results suggest that the combination of capsaicin and 6-gingerol has an additive effect on the inhibition of gastric acid secretion through activation of transient receptor potential vanilloid-1. In separate experiments, intraduodenal administration of either capsaicin (30 mg/kg) or 6-gingerol (15 mg/kg), whose doses were observed to have a significant inhibitory effect by oral administration, tended to inhibit basal acid secretion compared with the vehicle. These results suggest that the combination of capsaicin and 6-gingerol has an additive effect on inhibition of gastric acid secretion through activation of transient receptor potential vanilloid-1, and oral administration of transient receptor potential vanilloid-1 agonists directly stimulates transient receptor potential vanilloid-1 in the gastric lumen, resulting in a potent reduction of gastric acid secretion.
Keywords: capsaicin; 6-gingerol; transient receptor potential vanilloid-1; TRPV1; gastric acid secretion; mice